2016
DOI: 10.1120/jacmp.v17i2.5914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tracking accuracy of the CyberKnife system using a webcam and printed calibrated grid

Abstract: Tracking accuracy for the CyberKnife's Synchrony system is commonly evaluated using a film‐based verification method. We have evaluated a verification system that uses a webcam and a printed calibrated grid to verify tracking accuracy over three different motion patterns. A box with an attached printed calibrated grid and four fiducial markers was attached to the motion phantom. A target marker was positioned at the grid's center. The box was set up using the other three markers. Target tracking accuracy was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The SD of the Synchrony correlation error along any direction was ≤0.2 mm on average, indicating that CyberKnife's predictive model precisely reproduces fiducial (i.e., target) motion. This level of positional measurement agreement is consistent with CyberKnife tracking errors that other groups have found for the case of sinusoidal motion . If in turn, we look at the data for Model‐Fiducial which compares the same position datasets as the Synchrony correlation error but has had the coordinate alignment algorithm applied to the data, we see that in the primary direction of motion, z‐ direction (ANT/POST) and in the x direction (SUP/INF) the average SD of the differences is also ≤0.2 mm, however, in the y direction (LFT/RGT) the errors are higher (0.6 mm average SD).…”
Section: Discussionsupporting
confidence: 87%
“…The SD of the Synchrony correlation error along any direction was ≤0.2 mm on average, indicating that CyberKnife's predictive model precisely reproduces fiducial (i.e., target) motion. This level of positional measurement agreement is consistent with CyberKnife tracking errors that other groups have found for the case of sinusoidal motion . If in turn, we look at the data for Model‐Fiducial which compares the same position datasets as the Synchrony correlation error but has had the coordinate alignment algorithm applied to the data, we see that in the primary direction of motion, z‐ direction (ANT/POST) and in the x direction (SUP/INF) the average SD of the differences is also ≤0.2 mm, however, in the y direction (LFT/RGT) the errors are higher (0.6 mm average SD).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we also evaluated the impacts of the update of the correlation models by changing the interval of the KV image acquisitions. This evaluation was possible because our technique evaluates the treatment x‐ray beams, although other techniques using laser or head‐mounted camera cannot use TLS during measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have investigated the motion‐tracking accuracy of the SRTS . Inoue et al investigated the tracking accuracy using a video camera mounted on the CyberKnife head .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a real‐time evaluation technique for evaluating tracking accuracy is needed. Although a few studies have reported techniques to evaluate dynamic tracking errors using a video camera mounted on the linac head or laser equipped on the linac, these methods did not evaluate the radiation beams.…”
Section: Introductionmentioning
confidence: 99%